Respuesta :

frika

Answer:

D. [tex]-\dfrac{1}{2}[/tex]

Step-by-step explanation:

Given the fraction:

[tex]\dfrac{\dfrac{3}{4y}-\dfrac{2}{y}}{\dfrac{1}{y}+\dfrac{3}{2y}}[/tex]

Consider the numerator and the denominator separately:

Numerator:

[tex]\dfrac{3}{4y}-\dfrac{2}{y}=\dfrac{3}{4y}-\dfrac{8}{4y}=\dfrac{3-8}{4y}=-\dfrac{5}{4y}[/tex]

Denominator:

[tex]\dfrac{1}{y}+\dfrac{3}{2y}=\dfrac{2}{2y}+\dfrac{3}{2y}=\dfrac{2+3}{2y}=\dfrac{5}{2y}[/tex]

Now,

[tex]\dfrac{\dfrac{3}{4y}-\dfrac{2}{y}}{\dfrac{1}{y}+\dfrac{3}{2y}}=\dfrac{-\dfrac{5}{4y}}{\dfrac{5}{2y}}=-\dfrac{5}{4y}\div \dfrac{5}{2y}=-\dfrac{5}{4y}\times \dfrac{2y}{5}=-\dfrac{1}{2}[/tex]

ACCESS MORE